2008
DOI: 10.1177/0731684408095048
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bamboo/Glass Fiber Reinforced USP and VE Resin

Abstract: The effects of weight fraction and length of short bamboo and glass fibers on flexural strength and inter-laminar shear strength (ILSS) of vinyl ester resin and unsaturated polyester (USP) resins were investigated. The bamboo fibers were isolated from the bamboo plant by treating them with dilute solution of sodium hydroxide (0.1 and 1 N NaOH) for 72 h and then boiling them in a pressure cooker for 30 min. The fibers were separated, dried, and cut into 5 or 10 mm lengths. Composites were fabricated using vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Researchers stated that bamboo fibres can replace up to 25 wt.% of glass fibres without lowering mechanical properties of glass fibre based composites [81]. They observed that quantity of bamboo fibres loading gradually increases the modulus and strength of fabricated biocomposites.…”
Section: Comparison Of Bamboo Fibre Reinforced Composites With Convenmentioning
confidence: 97%
“…Researchers stated that bamboo fibres can replace up to 25 wt.% of glass fibres without lowering mechanical properties of glass fibre based composites [81]. They observed that quantity of bamboo fibres loading gradually increases the modulus and strength of fabricated biocomposites.…”
Section: Comparison Of Bamboo Fibre Reinforced Composites With Convenmentioning
confidence: 97%
“…Natural fibers like coir, jute, oil palm, sisal fibers have all been proved to be good reinforcement in thermoset and thermoplastic matrices 2–5. In our previous study, we have found that the replacement of glass fiber, upto a certain extent, by bamboo fibers to be an effective reinforcement in polyester matrix 6…”
Section: Introductionmentioning
confidence: 98%
“…Thus, composites with bamboo fiber reinforcements are emerging as realistic materials in the structural community because of their advantages such as low cost, acceptable specific properties, weather resistant, dimensional stability, and biodegradability over conventional composites . Mandal et al performed a comparative study on the mechanical properties of glass/bamboo fiber reinforced composites . The results show that there is no significant difference in the mechanical properties of composites under the condition that 25 wt% of glass fibers are substituted by bamboo fibers.…”
Section: Introductionmentioning
confidence: 99%